Pengembangan Edible Sensor Berbasis Ekstrak Kayu Secang dan Kubis Ungu untuk Deteksi Kesegaran Cumi - Annisa Zindagi Doa Reta Sarih (Fakultas Farmasi, 2026)
Monitoring the decline in food freshness is a critical concern in food safety, as deteriorating quality is typically marked by the accumulation of volatile basic compounds resulting from microbial activity and natural degradation processes. Consequently, there is an urgent need for food packaging indicators that are not only user-friendly and safe but also practical and highly sensitive. This study focuses on developing a smart packaging system designed to monitor the freshness of squid. The system utilizes sustainable, natural-based materials, specifically bacterial cellulose membranes derived from nata de coco, which are immobilized with purple cabbage and sappan wood (secang) extracts to serve as natural pH indicators. These extracts were prepared using the maceration method before being successfully immobilized into the cellulose matrix. The membranes underwent comprehensive characterization, including color change analysis, RGB value monitoring, color response across varying pH levels, functional group analysis, and morphological assessment. Furthermore, the application was tested on squid samples stored at both room and chiller temperatures, with freshness parameters monitored through pH, TVB-N, and Total Plate Count (TPC) assays. The results demonstrated distinct color shifts in both membranes corresponding to the squid's freshness levels. RGB analysis revealed significant shifts in 'mean green' for the purple cabbage indicator and 'mean red' for the sappan wood indicator. combination of purple cabbage and sappan wood proved to be an effective dual-sensor system due to its highly visible and distinct color transitions. Overall, both indicators successfully monitored and detected the freshness of squid during storage.
FINALISASI oleh Arif 2026 Juni 23
Keywords: smart packaging; freshness indicator; sappan wood; purple cabbage; bacterial cellulose; squid